HPV vaccination uptake among Somali American patients at an urban primary care clinic in Minnesota, USA: identifying and testing interventions to improve uptake using video reflexive ethnography. Issue 12 (30th December 2021) - Pratt, Rebekah; Ndagire, Channelle; Oyenuga, Abayomi; Xiong, Serena; Carroll, Katherine; Adam, Patricia
Abstract : Objectives: While there have been efforts to address common and culturally informed barriers to healthcare, Somali Americans have low rates of human papillomavirus (HPV) vaccination. This study aimed to use video reflexive ethnography (VRE) to identify primary care health inequities, derive interventions aimed at improving HPV vaccination rates in Somali Americans, and then test their impact on vaccination rates. Design: The VRE methodology involves three sequential steps: data collection, reflexive discussion and identifying intervention in practice. Preintervention and postintervention vaccination uptake data were collected for Somali patients. Setting: VRE was conducted with medical assistants (MAs) and Somali patients for 3 months (June–August 2018) in an urban primary care clinic in Minnesota, USA. HPV vaccination rates were collected and analysed pre-VRE and for a period of 6 months post the implementation of the interventions identified by VRE. Participants: 14 MAs participated in the VRE which designed the study intervention, which was tested on 324 Somali patients eligible for HPV vaccination. Primary outcome measure: HPV vaccination uptake among Somali patients. Results: MAs identified three practice challenges related to HPV vaccination: provider fatigue related to ongoing patient vaccine hesitancy or refusal, MAs misinterpretation of patient's vaccination dissent language, and missed opportunities to respond to unique patient concerns as a result of following standard work procedures. Using VRE, MAs identified and developed several interventions to address these practice challenges. Adjusted for age at clinic visit (years), the difference in preintervention and postintervention HPV immunisation rates was 10.1 per 100 patient-visits (95% CI 2.97 17.3; p=0.0057). Conclusion: VRE can engage MAs in an innovative, participatory process to identify and address concerns about health inequities. In this study, MAs designed and implemented interventions that improved HPV vaccination rates in Somali Americans. Further research is needed to more fully assess the impact of such interventions.